An??lise econ??mica do direito aplicada ao mercado imobili??rio nacional: reflexos do programa Minha Casa Minha Vida 2008 - 2013 - Santos, Gilc??lia de Paula (2017)
The present work consists of two essays and an experiment in which the behavior of the agents of the real estate market (Financial Institutions and alleged borrowers) is analyzed, using the Economic Analysis of Law combined with the Analytical-Behavioral Theory of Law. The objective of the work is to identify how these agents behave through the incentives granted by the Minha Casa, Minha Vida government program and the consequences of these behaviors in the real estate market. These studies are justified since the Federal Government has been working with the objective of reducing the country's housing deficit by means of actions to subsidize the acquisition of housing units for the lower income population, which are guided by a vast set of legal, Guiding the performance of individuals, builders and financial institutions, which ended up influencing the market, understood here as free interaction among the agents to perform barter trade.